Corundum self-flowing castable based on circulating refractory material and preparation method thereof
By using innovative processes such as circulating refractory materials and hydrated alumina, high-performance corundum self-flow castables are prepared, which solves the structural defects of existing materials after high temperature use, and achieves low-cost, high-strength and environmentally friendly refractory production.
Patent Information
- Application Number
- CN202311348974.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-10-18
AI Technical Summary
The existing corundum self-flow castable material is prone to structural defects after high temperature use, resulting in a decrease in strength and a shortened service life. At the same time, the production process of traditional refractory materials is highly energy-consuming and pollution-free, which violates environmental protection policies.
Materials such as circulating corundum aggregate, circulating high-voltage electric porcelain aggregate, defective spinel fine powder and chopped basalt fibers are used, combined with hydrated alumina as a binder and organic acid as a retarder, high-performance corundum self-flow castable with high binding strength, corrosion resistance and long service life are prepared.
It achieves low cost, high strength, pollution-free and corrosion-resistant materials, extends the service life of the materials, and reduces energy consumption and pollution emissions in the production process.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials for ladles, and in particular relates to a self-flowing corundum castable based on circulating refractory materials and a preparation method thereof. Background Art
[0002] With the rapid development of my country's high-temperature industry, the annual consumption of amorphous refractory materials exceeds 7 million tons, of which low- and medium-grade aluminum castables and spray coatings are the main ones. This has led to an increasing consumption of refractory mineral raw material resources, and the situation of increasingly scarce mineral raw materials has become increasingly severe. The production of refractory raw materials is a high-energy consumption and high-pollution process, which does not meet the requirements of national environmental protection policies. In order to achieve the goal of energy conservation and emission reduction in my country's refractory industry, effectively reduce the consumption of traditional refractory raw materials, and further improve the economy of refractory materials, the use of recycled solid waste refractory raw materials to replace traditional refractory raw materials is an important and urgent issue facing the development of my country's refractory industry.
[0003] Self-flowing castable is a new type of refractory material developed in the 1990s. Compared with ordinary castables, it has obvious advantages. It not only inherits the advantages of low-cement castables, such as high density, good refractory performance, corrosion resistance and wear resistance, but also can flow and solidify by itself without vibrating equipment during construction. With the development of ladle refining technology, the melting temperature and melting time have been successively increased, making the working environment of ladle refractory materials in actual use more and more harsh. Corundum self-flowing castable is mainly used to fill the gaps around air bricks and seat bricks. During use, it will be mechanically eroded by molten steel and argon blowing and stirring molten steel. Intermittent production will also bring large temperature fluctuations. At the end of casting, it will also be chemically eroded by ladle slag.
[0004] At present, most of the commonly used aluminum-magnesium and high-aluminum self-flowing castables are castables with low cement or ultra-low cement as binders, and a small amount of SiO2 powder is added to improve the fluidity of the self-flowing castable. Therefore, during use, the cement-bound castable is prone to generate low-melting-point phases such as calcite (with a melting point of about 1560°C) at a lower temperature. This causes the castable to sinter and shrink, affecting its high-temperature performance. In addition, SiO2 will also form SiO in a strong reducing atmosphere. x Gas phase, through the volatilization of acidic gas phase, causes material damage. The above reaction causes a large number of structural defects in self-flowing castables after being used at medium and high temperatures, resulting in a decrease in strength and a shortened service life.
[0005] At present, there are technologies for the preparation and performance optimization of corundum self-flowing castables, such as the patented technology of "Refractory material for ladle bottom and preparation method thereof" (CN103482992A), a patented technology for preparing aluminum-magnesium self-flowing castables using 60-88wt% of bauxite or corundum, 1-16wt% of magnesia, 5-14wt% of α-alumina micropowder, 2-10wt% of ρ-alumina micropowder and 0-2wt% of silicon micropowder as raw materials. The self-flowing castable prepared by this method has many defects in forming hydrates during the hydration process, and forms spinel at high temperature, which is easy to cause large volume expansion and has a short service life; such as "Self-flowing castable prepared by using waste materials of blast furnace iron trench cover and preparation method thereof" (CN1119608 08A) patent technology, discloses a patent technology for preparing high-alumina self-flowing castables with 15-25 parts of iron ditch cover waste, 30-60 parts of brown corundum clinker, 10-20 parts of white corundum, 15-25 parts of silicon carbide, 4-9 parts of silicon micropowder, 5-10 parts of activated alumina powder, 3-8 parts of pure calcium aluminate cement, 3-5 parts of expansion agent, 0.5-1 part of water reducer, and 0.05-1 part of explosion-proof agent as raw materials. In this method, the amount of silicon micropowder is large and the use temperature is limited; such as the patent technology of "Nano-silica sol combined with furnace hearth self-flowing material and its preparation method" (CN105732052A), discloses a patent technology for preparing high-alumina self-flowing castables with 65-80 parts of corundum, 8-20 parts of silicon carbide, 5-10 parts of activated alumina micropowder, 2-5 parts of silicon dioxide micropowder, spherical The patented technology of preparing corundum self-flowing castable material is characterized in that the spherical asphalt used as a binder is a petrochemical by-product, which is easy to pollute the environment and increase the carbon content of molten iron, which is not conducive to the improvement of the quality of smelting products; for example, the patented technology of "high-aluminum self-flowing castable material based on recycled refractory materials and preparation method thereof" (CN115340370A) discloses a method of preparing a self-flowing castable material with recycled corundum aggregate and 25.0-34.0wt% recycled zirconium corundum aggregate, 13.0-19.0wt% recycled spinel fine powder, 6.0-9.0wt% alpha alumina, A patented technology for preparing high-alumina self-flowing castables using 2.0-5.0wt% fluorite slag and 1.5-4.5wt% hydratable alumina as raw materials. The fluorite slag used in this method will enhance the reaction between the material and the slag, thereby increasing the corrosion rate of the material and shortening its life; another example is "Research and Development of New Corundum Self-flowing Castables and Their Application in Ladles" ("Refractory and Lime" 2023 Vol. 48, No. 1, P8-11), which discloses a technology for preparing corundum self-flowing castables using calcium titanate aggregate, white corundum aggregate, activated alumina powder, calcined alumina powder, calcium aluminate cement, and silicon powder as raw materials, plus a certain amount of dispersant and water reducer. The binder used in this method is calcium aluminate cement, which is easy to cause Ca pollution to the molten steel.
[0006] The present invention uses recycled corundum aggregate, recycled high-voltage electric porcelain aggregate, recycled defective spinel and used chopped basalt fiber as main raw materials to prepare high-performance corundum self-flowing castable with excellent bonding performance, strong stable dispersibility and good corrosion resistance. While realizing the Ca-free of the corundum self-flowing castable, the low cost of the corundum self-flowing castable and the extended service life can also be achieved. Summary of the invention
[0007] The present invention aims to overcome the defects of the prior art and aims to provide a stable, efficient, green and low-cost self-flowing corundum castable based on recycled refractory materials and a preparation method thereof. The self-flowing corundum castable based on recycled refractory materials prepared by the method has high bonding strength, excellent corrosion resistance and long service life, which is of great significance to the promotion of my country's bulk solid waste recycling industry.
[0008] To achieve the above purpose, the technical scheme adopted by the present invention is: first, 35.0-47.0wt% of recycled corundum aggregate and 25.0-34.0wt% of recycled high-voltage porcelain aggregate, 13.0-19.0wt% of defective spinel fine powder, 6.0-9.0wt% of active α-alumina, 2.0-5.0wt% of brown corundum dust removal powder, 1.5-4.5wt% of hydratable alumina are used as raw materials, and then 4.5-6.5wt% of water, 3.5-4.5wt% of retarder, 1.5-2.5wt% of stabilizer and 0.05-0.08wt% of recycled basalt fiber are added and mixed evenly to obtain a corundum self-flowing castable based on recycled refractory materials.
[0009] The recycled corundum aggregate is derived from recycled materials of discarded ladle seat bricks and air-permeable bricks, wherein: particles with a particle size between 8 and 5 mm account for 35.0wt%, particles with a particle size between 5 and 3 mm account for 19.0wt%, particles with a particle size between 3 and 1 mm account for 16.0wt%, particles with a particle size between 1 and 0.088 mm account for 8.0wt%, and fine powder with a particle size less than 0.088 mm accounts for 22.0wt%; the main chemical components of the recycled corundum aggregate are: Al2O3 content ≥97.5wt%, Na2O content ≤0.5wt%, and Fe2O3 content ≤0.3wt%.
[0010] The recycled high-voltage porcelain aggregate is derived from crushed high-voltage porcelain after use, wherein: particles with a particle size between 5 and 3 mm account for 27.0wt%, particles with a particle size between 3 and 1 mm account for 35.0wt%, particles with a particle size between 1 and 0.088 mm account for 22.0wt%, and fine powder with a particle size less than 0.088 mm accounts for 16.0wt%; the main chemical components of the recycled high-voltage porcelain aggregate are: Al2O3 content ≥49.0wt%, SiO2 content ≥37.0wt%, MgO content ≤3.1wt%, Na2O content ≤0.7wt%, K2O content ≤0.5wt%, and Fe2O3 content ≤0.2wt%.
[0011] The defective spinel fine powder is obtained by screening after crushing the rear electric furnace lining, wherein: particles with a particle size between 1 and 0.088 mm account for 33.0wt%, particles with a particle size between 0.088 and 0.045 mm account for 52.0wt%, and fine powder with a particle size less than 0.045 mm accounts for 15.0wt%; the main chemical components of the defective spinel fine powder are: MgO content ≥49.0wt%, Al2O3 content ≥25.0wt%, Fe2O3 content ≥19.0wt%, SiO2 content ≤3.5wt%, Fe2O3 content ≤1.2wt%, IL ≤0.2wt%.
[0012] The particle size of the activated α-alumina is less than 0.5 μm; the main chemical components of the activated α-alumina are: Al2O3 content ≥ 99.2wt%, Na2O content ≤ 0.05wt%.
[0013] The brown corundum dust removal powder is a solid industrial waste gas collected by bag dust removal during the production process of fused brown corundum, and its particle size is less than 0.088mm; the main chemical components of the brown corundum dust removal powder are: SiO2 content ≥36.7wt%, Al2O3 content ≥30.5wt%, and Fe2O3 content ≤1.9wt%.
[0014] The particle size of the hydrated alumina is less than 0.074 mm; the main chemical components of the hydrated alumina are: Al2O3 content ≥ 64.5wt%, Na2O content ≤ 0.15wt%, IL ≤ 18.9wt%.
[0015] The retarder is one of citric acid, tartaric acid or phosphoric acid.
[0016] The stabilizer is one of magnesium aluminum silicate sol or magnesium aluminum silicate composite silica sol.
[0017] The recycled basalt fiber is chopped into 3-5 mm after use; the main chemical components of the basalt fiber are: SiO2 content ≥42.6wt%, Al2O3 content ≥21.1wt%, MgO content ≥17.0wt%, MgO content ≥9.0wt%, and Fe2O3 content ≤1.9wt%.
[0018] Due to the adoption of the above technical solution, the present invention has the following positive effects compared with the prior art:
[0019] 1. Low cost and high strength - using recycled corundum aggregate and recycled high-voltage electric porcelain aggregate to replace the conventionally selected plate-shaped corundum, white corundum or mullite can relieve energy pressure and be green and environmentally friendly; using recycled defective spinel fine powder to replace sintered spinel fine powder can not only effectively reduce the expansion caused by the in-situ sintering of spinel, but also make full use of the oxygen vacancies rich in recycled defective spinel to absorb and dissolve heterogeneous elements in the slag; the prepared corundum self-flowing castable based on recycled refractory materials has better performance than similar products on the market: flexural strength 12.9~17.1MPa (110℃×24h), compressive strength 69.4~81.6MPa (110℃×24h).
[0020] 2. No pollution, high corrosion resistance - using hydrated alumina to replace calcium aluminate cement as a conventional choice of binder, realizing the Ca-free of corundum self-flowing castables based on circulating refractory materials, avoiding the production of a large amount of low-melting products such as calcite during high-temperature use, optimizing the high-temperature performance of the castable, and extending the service life. Using organic acid as a retarder is beneficial to inhibit the hydrolysis reaction of hydrated alumina in the matrix, and on the other hand, organic acid can hydrolyze to form a large amount of OH- ions, so that the AlOOH sol formed by hydration is adsorbed on the surface of the particles, forming a new ceramic bonding reinforcement phase at high temperature, and further optimizing the material's corrosion resistance.
[0021] 3. Good stability and low attenuation rate - High-voltage insulators are exposed to the air for a long time, and weathering and electrical breakdown make them have super high hydrophobic properties. Their water absorption rate is much lower than that of ordinary corundum or aluminum silicon raw materials with similar chemical composition. High-voltage insulators with low water absorption rate can effectively reduce the amount of water added to the self-flowing material. During the static process, the high-voltage insulators with hydrophobic properties can be dispersed in the slurry and continue to maintain a discrete state, so that the self-flowing material shows a good initial self-flowing value and a longer self-flowing performance, and there will be no flow attenuation and construction failure as time goes on.
[0022] Therefore, the present invention has the characteristics of stability, high efficiency, green environmental protection and low cost; the corundum self-flowing castable based on the circulating refractory material has high bonding strength, excellent corrosion resistance and long service life. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with specific implementation modes, which is not intended to limit the protection scope of the present invention.
[0024] To avoid repetition, the relevant technical parameters involved in this specific implementation are first described as follows, and will not be repeated in the embodiments:
[0025] The recycled corundum aggregate is derived from recycled materials of discarded ladle seat bricks and air-permeable bricks, wherein: particles with a particle size between 8 and 5 mm account for 35.0wt%, particles with a particle size between 5 and 3 mm account for 19.0wt%, particles with a particle size between 3 and 1 mm account for 16.0wt%, particles with a particle size between 1 and 0.088 mm account for 8.0wt%, and fine powder with a particle size less than 0.088 mm accounts for 22.0wt%; the main chemical components of the recycled corundum aggregate are: Al2O3 content ≥97.5wt%, Na2O content ≤0.5wt%, and Fe2O3 content ≤0.3wt%.
[0026] The recycled high-voltage porcelain aggregate is derived from crushed high-voltage porcelain after use, wherein: particles with a particle size between 5 and 3 mm account for 27.0wt%, particles with a particle size between 3 and 1 mm account for 35.0wt%, particles with a particle size between 1 and 0.088 mm account for 22.0wt%, and fine powder with a particle size less than 0.088 mm accounts for 16.0wt%; the main chemical components of the recycled high-voltage porcelain aggregate are: Al2O3 content ≥49.0wt%, SiO2 content ≥37.0wt%, MgO content ≤3.1wt%, Na2O content ≤0.7wt%, K2O content ≤0.5wt%, and Fe2O3 content ≤0.2wt%.
[0027] The defective spinel fine powder is obtained by screening after crushing the rear electric furnace lining, wherein: particles with a particle size between 1 and 0.088 mm account for 33.0wt%, particles with a particle size between 0.088 and 0.045 mm account for 52.0wt%, and fine powder with a particle size less than 0.045 mm accounts for 15.0wt%; the main chemical components of the defective spinel fine powder are: MgO content ≥49.0wt%, Al2O3 content ≥25.0wt%, Fe2O3 content ≥19.0wt%, SiO2 content ≤3.5wt%, Fe2O3 content ≤1.2wt%, IL ≤0.2wt%.
[0028] The particle size of the activated α-alumina is less than 0.5 μm; the main chemical components of the activated α-alumina are: Al2O3 content ≥ 99.2wt%, Na2O content ≤ 0.05wt%.
[0029] The brown corundum dust removal powder is a solid industrial waste gas collected by bag dust removal during the production process of fused brown corundum, and its particle size is less than 0.088mm; the main chemical components of the brown corundum dust removal powder are: SiO2 content ≥36.7wt%, Al2O3 content ≥30.5wt%, and Fe2O3 content ≤1.9wt%.
[0030] The particle size of the hydrated alumina is less than 0.074 mm; the main chemical components of the hydrated alumina are: Al2O3 content ≥ 64.5wt%, Na2O content ≤ 0.15wt%, IL ≤ 18.9wt%.
[0031] The retarder is one of citric acid, tartaric acid or phosphoric acid.
[0032] The stabilizer is one of magnesium aluminum silicate sol or magnesium aluminum silicate composite silica sol.
[0033] The recycled basalt fiber is chopped into 3-5 mm after use; the main chemical components of the basalt fiber are: SiO2 content ≥42.6wt%, Al2O3 content ≥21.1wt%, MgO content ≥17.0wt%, MgO content ≥9.0wt%, and Fe2O3 content ≤1.9wt%.
[0034] Example 1
[0035] A self-flowing corundum castable based on circulating refractory materials and a preparation method thereof. First, 35.0-37.0wt% of circulating corundum aggregate and 32.5-34.0wt% of circulating high-voltage electric porcelain aggregate, 14.0-15.0wt% of defective spinel fine powder, 7.5-8.0wt% of active α-alumina, 4.5-5.0wt% of brown corundum dust removal powder, and 4.0-4.5wt% of hydratable alumina are used as raw materials, and then 4.5-5.0wt% of water, 3.5-4.0wt% of citric acid, 1.5-2.5wt% of magnesium aluminum silicate sol and 0.05-0.08wt% of circulating basalt fiber are added and mixed evenly to obtain a self-flowing corundum castable based on circulating refractory materials.
[0036] The corundum self-flowing castable based on the circulating refractory material prepared in this embodiment is tested: after baking at 110°C×24h, the flexural strength is 14.2-16.5MPa, the compressive strength is 73.1-75.9MPa, and the strength retention rate after 20 times of thermal shock resistance test at 1100°C is greater than 62%.
[0037] Example 2
[0038] A self-flowing corundum castable based on circulating refractory materials and a preparation method thereof. First, 32.5-34.0wt% of circulating corundum aggregate and 31.0-32.5wt% of circulating high-voltage electric porcelain aggregate, 18.0-19.0wt% of defective spinel fine powder, 6.0-6.5wt% of active α-alumina, 4.0-4.5wt% of brown corundum dust removal powder, and 3.5-4.0wt% of hydratable alumina are used as raw materials, and then 5.0-5.5wt% of water, 4.0-4.5wt% of tartaric acid, 1.5-2.5wt% of magnesium aluminum silicate composite silica sol and 0.05-0.08wt% of circulating basalt fiber are added and mixed evenly to obtain a self-flowing corundum castable based on circulating refractory materials.
[0039] The corundum self-flowing castable based on the circulating refractory material prepared in this embodiment is tested: after baking at 110°C×24h, the flexural strength is 14.4-16.3MPa, the compressive strength is 75.1-78.4MPa, and the strength retention rate after 20 times of thermal shock resistance test at 1100°C is greater than 67%.
[0040] Example 3
[0041] A self-flowing corundum castable based on circulating refractory materials and a preparation method thereof. First, 39.0-41.0wt% of circulating corundum aggregate and 29.5-31.0wt% of circulating high-voltage electric porcelain aggregate, 15.0-16.0wt% of defective spinel fine powder, 8.5-9.0wt% of active α-alumina, 3.5-4.0wt% of brown corundum dust removal powder, and 3.0-3.5wt% of hydratable alumina are used as raw materials, and then 5.5-6.0wt% of water, 3.5-4.0wt% of phosphoric acid, 1.5-2.5wt% of magnesium aluminum silicate sol and 0.05-0.08wt% of circulating basalt fiber are added and mixed evenly to obtain a self-flowing corundum castable based on circulating refractory materials.
[0042] The corundum self-flowing castable based on the circulating refractory material prepared in this embodiment is tested: after baking at 110°C×24h, the flexural strength is 13.5-15.7MPa, the compressive strength is 72.7-76.1MPa, and the strength retention rate after 20 times of thermal shock resistance test at 1100°C is greater than 63%.
[0043] Example 4
[0044] A self-flowing corundum castable based on circulating refractory materials and a preparation method thereof. First, 45.0-47.0wt% of circulating corundum aggregate and 28.0-29.5wt% of circulating high-voltage electric porcelain aggregate, 13.0-14.0wt% of defective spinel fine powder, 6.5-7.0wt% of active α-alumina, 3.0-3.5wt% of brown corundum dust removal powder, and 2.0-2.5wt% of hydratable alumina are used as raw materials, and then 6.0-6.5wt% of water, 4.0-4.5wt% of citric acid, 1.5-2.5wt% of magnesium aluminum silicate composite silica sol and 0.05-0.08wt% of circulating basalt fiber are added and mixed evenly to obtain a self-flowing corundum castable based on circulating refractory materials.
[0045] The corundum self-flowing castable based on the circulating refractory material prepared in this embodiment is tested: after baking at 110°C×24h, the flexural strength is 12.9-14.2MPa, the compressive strength is 69.4-73.1MPa, and the strength retention rate after 20 times of thermal shock resistance test at 1100°C is greater than 65%.
[0046] Example 5
[0047] A self-flowing corundum castable based on circulating refractory materials and a preparation method thereof. First, 41.0-43.0wt% of circulating corundum aggregate and 26.5-28.0wt% of circulating high-voltage electric porcelain aggregate, 17.0-18.0wt% of defective spinel fine powder, 7.0-7.5wt% of active α-alumina, 2.5-3.0wt% of brown corundum dust removal powder, and 2.5-3.0wt% of hydratable alumina are used as raw materials, and then 5.5-6.0wt% of water, 3.5-4.0wt% of tartaric acid, 1.5-2.5wt% of magnesium aluminum silicate sol and 0.05-0.08wt% of circulating basalt fiber are added and mixed evenly to obtain a self-flowing corundum castable based on circulating refractory materials.
[0048] The corundum self-flowing castable based on the circulating refractory material prepared in this embodiment is tested: after baking at 110°C×24h, the flexural strength is 13.8-15.5MPa, the compressive strength is 70.9-74.2MPa, and the strength retention rate after 20 times of thermal shock resistance test at 1100°C is greater than 69%.
[0049] Example 6
[0050] A self-flowing corundum castable based on circulating refractory materials and a preparation method thereof. First, 43.0-45.0wt% of circulating corundum aggregate and 25.0-26.5wt% of circulating high-voltage electric porcelain aggregate, 16.0-17.0wt% of defective spinel fine powder, 8.0-8.5wt% of active α-alumina, 2.0-2.5wt% of brown corundum dust removal powder, and 1.5-2.0wt% of hydratable alumina are used as raw materials, and then 4.5-5.0wt% of water, 3.5-4.0wt% of retarder, 1.5-2.5wt% of magnesium aluminum silicate composite silica sol and 0.05-0.08wt% of circulating basalt fiber are added and mixed evenly to obtain a self-flowing corundum castable based on circulating refractory materials.
[0051] The corundum self-flowing castable based on the circulating refractory prepared in this embodiment is tested: after baking at 110°C×24h, the flexural strength is 14.8-16.1MPa, the compressive strength is 77.2-81.6MPa, and the strength retention rate after 20 times of thermal shock resistance test at 1100°C is greater than 74%.
[0052] Due to the adoption of the above technical solution, this specific implementation has the following positive effects compared with the prior art:
[0053] 1. Low cost and high strength - using recycled corundum aggregate and recycled high-voltage electric porcelain aggregate to replace the conventionally selected plate-shaped corundum, white corundum or mullite can relieve energy pressure and be green and environmentally friendly; using recycled defective spinel fine powder to replace sintered spinel fine powder can not only effectively reduce the expansion caused by the in-situ sintering of spinel, but also make full use of the oxygen vacancies rich in recycled defective spinel to absorb and dissolve heterogeneous elements in the slag; the prepared corundum self-flowing castable based on recycled refractory materials has better performance than similar products on the market: flexural strength 12.9~17.1MPa (110℃×24h), compressive strength 69.4~81.6MPa (110℃×24h).
[0054] 2. No pollution, high corrosion resistance - using hydrated alumina to replace calcium aluminate cement as a conventional choice of binder, realizing the Ca-free of corundum self-flowing castables based on circulating refractory materials, avoiding the production of a large amount of low-melting products such as calcite during high-temperature use, optimizing the high-temperature performance of the castable, and extending the service life. Using organic acid as a retarder is beneficial to inhibit the hydrolysis reaction of hydrated alumina in the matrix, and on the other hand, organic acid can hydrolyze to form a large amount of OH- ions, so that the AlOOH sol formed by hydration is adsorbed on the surface of the particles, forming a new ceramic bonding reinforcement phase at high temperature, and further optimizing the material's corrosion resistance.
[0055] 3. Good stability and low attenuation rate - High-voltage insulators are exposed to the air for a long time, and weathering and electrical breakdown make them have super high hydrophobic properties. Their water absorption rate is much lower than that of ordinary corundum or aluminum silicon raw materials with similar chemical composition. High-voltage insulators with low water absorption rate can effectively reduce the amount of water added to the self-flowing material. During the static process, the high-voltage insulators with hydrophobic properties can be dispersed in the slurry and continue to maintain a discrete state, so that the self-flowing material shows a good initial self-flowing value and a longer self-flowing performance, and there will be no flow attenuation and construction failure as time goes on.
[0056] Therefore, the present invention has the characteristics of stability, high efficiency, green environmental protection and low cost; the corundum self-flowing castable based on recycled refractory materials has high bonding strength, excellent corrosion resistance and long service life, which is of great significance to the promotion of the recycling industry of bulk solid waste.
Claims
1. A method for preparing a self-flowing corundum castable based on circulating refractory materials, characterized in that First, 35.0~47.0wt% of recycled corundum aggregate and 25.0~34.0wt% of recycled high-voltage porcelain aggregate, 13.0~19.0wt% of defective spinel fine powder, 6.0~9.0wt% of active α alumina, 2.0~5.0wt% of brown corundum dust removal powder, 1.5~4.5wt% of hydratable alumina are used as raw materials, and then 4.5~6.5wt% of water, 3.5~4.5wt% of retarder, 1.5~2.5wt% of stabilizer and 0.0 5~0.08wt% of recycled basalt fiber are mixed evenly to obtain a corundum self-flowing castable based on recycled refractory materials; the stabilizer is one of magnesium aluminum silicate sol or magnesium aluminum silicate composite silica sol; the main chemical components of the recycled high-voltage porcelain aggregate are: Al2O3 content ≥49.0wt%, SiO2 content ≥37.0wt%, MgO content ≤3.1wt%, Na2O content ≤0.7wt%, K2O content ≤0.5wt%, and Fe2O3 content ≤0.2wt%.
2. The method for preparing a self-flowing corundum castable based on circulating refractory material according to claim 1, characterized in that The recycled corundum aggregate comes from the recycled materials of discarded ladle seat bricks and air bricks, among which: particles with a particle size between 8 and 5 mm account for 35.0wt%, particles with a particle size between 5 and 3mm account for 19.0wt%, particles with a particle size between 3 and 1mm account for 16.0wt%, particles with a particle size between 1 and 0.088mm account for 8.0wt%, and fine powder with a particle size less than 0.088mm accounts for 22.0wt%; the main chemical components of the recycled corundum aggregate are: Al2O3 content ≥97.5wt%, Na2O content ≤0.5wt%, and Fe2O3 content ≤0.3wt%.
3. The method for preparing a self-flowing corundum castable based on a circulating refractory material according to claim 1, characterized in that The recycled high-voltage porcelain aggregate comes from crushed high-voltage porcelain after use, wherein: particles with a particle size between 5 and 3 mm account for 27.0 wt%, particles with a particle size between 3 and 1 mm account for 35.0 wt%, particles with a particle size between 1 and 0.088 mm account for 22.0 wt%, and fine powder with a particle size less than 0.088 mm accounts for 16.0 wt%.
4. The method for preparing a self-flowing corundum castable based on a circulating refractory material according to claim 1, characterized in that The defective spinel fine powder is obtained by screening after crushing the rear electric furnace lining, wherein: particles with a particle size between 1 and 0.088 mm account for 33.0wt%, particles with a particle size between 0.088 and 0.045 mm account for 52.0wt%, and fine powder with a particle size less than 0.045 mm accounts for 15.0wt%; the main chemical components of the defective spinel fine powder are: MgO content ≥49.0wt%, Al2O3 content ≥25.0wt%, Fe2O3 content ≥19.0wt%, SiO2 content ≤3.5wt%, Fe2O3 content ≤1.2wt%, IL ≤0.2wt%.
5. The method for preparing a self-flowing corundum castable based on circulating refractory material according to claim 1, characterized in that The particle size of the activated α alumina is less than 0.5 μm; the main chemical components of the activated α alumina are: Al2O3 content ≥ 99.2wt%, Na2O content ≤ 0.05wt%.
6. The method for preparing a self-flowing corundum castable based on a circulating refractory material according to claim 1, characterized in that The brown corundum dust removal powder is a solid industrial waste gas collected by bag dust removal during the production process of electrofused brown corundum, and its particle size is less than 0.088mm; the main chemical components of the brown corundum dust removal powder are: SiO2 content ≥36.7wt%, Al2O3 content ≥30.5wt%, and Fe2O3 content ≤1.9wt%.
7. The method for preparing a self-flowing corundum castable based on circulating refractory material according to claim 1, characterized in that The particle size of the hydrated alumina is less than 0.074 mm; the main chemical components of the hydrated alumina are: Al2O3 content ≥ 64.5wt%, Na2O content ≤ 0.15wt%, IL ≤ 18.9wt%.
8. The method for preparing a self-flowing corundum castable based on circulating refractory material according to claim 1, characterized in that The retarder is one of citric acid, tartaric acid or phosphoric acid.
9. The method for preparing a self-flowing corundum castable based on circulating refractory material according to claim 1, characterized in that The recycled basalt fiber is used basalt fiber chopped into 3-5 mm; the main chemical components of the basalt fiber are: SiO2 content ≥42.6wt%, Al2O3 content ≥21.1wt%, MgO content ≥17.0wt%, MgO content ≥9.0wt%, and Fe2O3 content ≤1.9wt%.
10. A self-flowing corundum castable based on a circulating refractory material, wherein the self-flowing corundum castable based on a circulating refractory material is a self-flowing corundum castable based on a circulating refractory material obtained by the preparation method of the self-flowing corundum castable based on a circulating refractory material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Fireproof material for steel ladle bottom and preparation method thereof
CN103482992A
Nano silica sol combination hearth self-flowing material and preparation method thereof
CN105732052A
Self-flowing castable prepared from blast furnace iron runner cover waste and preparation method thereof
CN111960808A
High-alumina self-flowing castable based on used refractory material and preparation method thereof
CN115340370A
Low-expansion refractory castable used for induction heating furnace and prepared from high-voltage electric porcelain reclaimed material
CN116003144A